(untitled) (Eurasian Journal of Physics,Chemistry and Mathematics, 2023)
In the current study, we investigate the effect of (Pb) substitution instead of (Bi) on the properties of the superconductor compound (Bi2-xPbxBa2Can-1CunO10+δ) with (x=0,0.05,0.1,0.15,0.2). The samples were prepared by solid state reaction method(SSR). X-ray diffraction technique (XRD) was used to estimate the structural properties of the specimens which show an orthorhombic crystalline structure for all the specimens. X-ray diffraction analysis of the pure and substituted analysis showed that all samples contain a high percentage of high phase (Bi-2223) in addition to some other phases with a few impurities at the end of the chart and an increase in the intensity of the high phase peaks (Bi-2223) .